2013
DOI: 10.1016/j.adt.2011.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Table of experimental nuclear ground state charge radii: An update

Abstract: The present table contains experimental root-mean-square (rms) nuclear charge radii R obtained by combined analysis of two types of experimental data: (i) radii changes determined from optical and, to a lesser extent, K α X-ray isotope shifts and (ii) absolute radii measured by muonic spectra and electronic scattering experiments. The table combines the results of two working groups, using respectively two different methods of evaluation, published in ADNDT earlier. It presents an updated set of rms charge rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

65
1,163
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,466 publications
(1,282 citation statements)
references
References 53 publications
65
1,163
1
6
Order By: Relevance
“…15, the charge radii calculated by the RCHB theory with PC-PK1 are shown as a function of neutron number in comparison with the data available. The charge radii in the RCHB calculations reproduce the experiment quite well for the nuclei with data available [90], and the charge radii of the nuclei without experimental data are predicted.…”
Section: Radii Of Nucleon Distributions 431 Charge Radiisupporting
confidence: 55%
See 2 more Smart Citations
“…15, the charge radii calculated by the RCHB theory with PC-PK1 are shown as a function of neutron number in comparison with the data available. The charge radii in the RCHB calculations reproduce the experiment quite well for the nuclei with data available [90], and the charge radii of the nuclei without experimental data are predicted.…”
Section: Radii Of Nucleon Distributions 431 Charge Radiisupporting
confidence: 55%
“…The binding energy per nucleon E b /A, two-neutron S 2n , two-proton S 2p , one-neutron S n and one-proton separation energy S p for each nucleus are also provided. In addition, the available experimental binding energies [6] and charge radii [90] are shown for comparison. There are totally 9035 nuclei from O(Z = 8) to Z = 120 which are predicted to be bound by the RCHB theory with the relativistic density functional PC-PK1.…”
Section: Nuclear Massmentioning
confidence: 99%
See 1 more Smart Citation
“…[27]. We have found that there is agreement to all digits presented for bindingenergy shifts calculated using the step-function density expression for the Uehling potential, Eq.…”
Section: Finite-size Uehling Potentialmentioning
confidence: 67%
“…We take the nuclear density to correspond to the two-parameter Fermi distribution, with the nuclear thickness (90% to 10% fall-off) taken to be 2.3 fm for all atoms and the half-density radii found from the root-mean-square radii of Ref. [27]. For E119, we take r rms = 6.5 fm, within the range predicted from HartreeFock-BCS theory [29].…”
Section: First-order Shiftsmentioning
confidence: 99%